Proceso atención de enfermería en recién nacido con sepsis neonatal. - Sánchez Vega, Adrián Vinicio (2021)
Neonatal sepsis is a risk factor for complications after birth developing a massive and invasive infection, the realization of this clinical case is in order to analyze the different situations that occur with a neonate diagnosed with sepsis detailing a newborn of 37 weeks of gestation with a history of urinary tract infections during pregnancy, presenting vomiting, diarrhea and stomach distention. The treatment is carried out with hydration and medication. The main objective of this study is clinical is the application of the nursing care process in newborns with neonatal sepsis.This care plan is more detailed, so it was carried out in a pediatric patient, choosing the patterns that are dysfunctional such as the Nutritional Pattern Metabolic and Elimination and Exchanges, this led us to analyze the Nursing Diagnoses that described the symptoms of the pediatric patient, applying the activities that allowed the positive evolution and improvement during their hospital admission. We conclude that an adequate assessment and the choice of priority activities contributed to recovery along with medical treatment. This clinical study also made it possible to identify risk factors for neonatal sepsis such as preterm birth, prolonged rupture of ovular membranes, and meconium amniotic fluid.